Analisis Strategi Komunikasi LKSA Yaatama dalam Membangun Kepercayaan Donatur pada Program Santunan Bulanan - Revalina Olivia Hendser; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the communication strategies employed by the Child Social Welfare Institution (LKSA) Yaatama to build trust specifically regarding integrity and transparency among regular donors of its monthly financial aid program. A descriptive qualitative research method was used, with data collected through observation, documentation, and in-depth interviews with institution administrators and donor representatives. The results indicate that LKSA Yaatama utilizes a two-way communication strategy by leveraging WhatsApp for personal, direct messaging to share detailed accountability reports. This medium is considered effective under Media Richness Theory, as it enables the transmission of rich content such as text, PDF documents, and visual records that validates the distribution of funds. Additionally, an interpersonal communication approach involving door-to-door visits is maintained to foster emotional closeness and demonstrate benevolence. Challenges such as information overload and varying donor personalities are mitigated through routine evaluations and a humanistic approach. In conclusion, consistent information transparency and warm personal interactions are the key factors in maintaining the loyalty of regular donors.